Time Is Not More Abstract Than Space in Sound - Kranjec, Alexander; Lehet, Matthew; Woods, Adam J.; Chatterjee, Anjan (Frontiers in Psychology, 2019)
Time is talked about in terms of space more frequently than the other way around. Some have suggested that this asymmetry runs deeper than language. The idea that we think about relatively abstract domains (like time) in terms of more concrete domains (like space) but not vice versa can be traced to conceptual metaphor theory. This theoretical account has some empirical support. Previous experiments suggest a deep ontological basis for space-time asymmetries. However, these studies frequently involve verbal and/or visual stimuli. Because vision makes a privileged contribution to spatial processing it is unclear whether these results speak to a deep asymmetry between time and space, or reflect a modality specific one. The present study was motivated by this uncertainty and what appears to be audition's privileged contribution to temporal processing. In Experiment 1, using an auditory perceptual task, duration and spatial displacement judgments were shown to be mutually contagious. Irrelevant temporal information influenced spatial judgments and vice versa with a larger effect of time on space. Experiment 2 examined the mutual effects of space, time, and pitch, a uniquely auditory attribute. If space is more abstract than time in sound, space should be more easily contaminated by pitch, while being less effective in contaminating it. While time and pitch were shown to be mutually contagious in Experiment 2, pitch affected estimates of space but not vice versa. Results overall suggest that the perceptual asymmetry between domains does not generalize across modalities and that time is not fundamentally more abstract than space.